2020
DOI: 10.1021/acs.jafc.9b07687
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Exploration of Potentially Bioactive Peptides in Casein Hydrolysates against Liver Oxidative Damage in STZ/HFD-Induced Diabetic Rats

Abstract: Hyperglycemia-induced oxidative stress can cause liver damage in diabetes, and protein hydrolysates with antidiabetic and antioxidant properties are emerging as a potential therapy. In this study, protective effects of casein hydrolysates against live oxidative damage in streptozotocin/high-fat-induced diabetic rats were studied and potentially bioactive peptides were explored by an integrated approach of differential peptide and in silico analysis. Results showed that different casein hydrolysates significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 54 publications
2
22
0
Order By: Relevance
“…28 Low MW peptides (<3 kDa) have been found to be the most potential bioactive peptides in many studies, and polypeptides with higher hydrophobicity have been shown to penetrate the cell membrane more easily to reach the target location. 29 In our study, 60.7% of the peptides in FMPH had a molecular weight less than 3 kDa, and over 50% of the amino acids were hydrophobic, suggesting their potential biological activities.…”
Section: Food and Function Papermentioning
confidence: 48%
“…28 Low MW peptides (<3 kDa) have been found to be the most potential bioactive peptides in many studies, and polypeptides with higher hydrophobicity have been shown to penetrate the cell membrane more easily to reach the target location. 29 In our study, 60.7% of the peptides in FMPH had a molecular weight less than 3 kDa, and over 50% of the amino acids were hydrophobic, suggesting their potential biological activities.…”
Section: Food and Function Papermentioning
confidence: 48%
“…However, commonly used sedative drugs such as morphine and phenobarbital had serious side effects such as dizzy feeling, excessive sedation, and even addiction . Recently, bioactive peptides and hydrolysates were used to be a supportive therapy, such as for insomnia, diabetes, and memory deficits problems. For instance, several natural proteins were found to contain encrypted peptides with anxiolytic and sleep-enhancing effects in their sequences, such as casein-derived decapeptide α-casozepine (YLGYLEQLLR, α-CZP) and undecapeptide (FLSSTEAQQSY) from soy β-conglycinin. , The αS1-casein tryptic hydrolysate (CTH) containing α-CZP was proven to alleviate anxiety and insomnia that was related with GABA A R in many studies, including intraperitoneal (i.p.) or oral administration (p.o.)…”
Section: Introductionmentioning
confidence: 99%
“…T2DM is often accompanied by insulin resistance, which can lead to reduced glycogen synthesis and storage. 40,41 Therefore, this study measured liver glycogen content and found that the model group had less glycogen synthesis. Following intervention with different metformin and anthocyanin treatments, glycogen synthesis tended to match control values.…”
Section: Resultsmentioning
confidence: 89%